Institutional factor for dropout in higher education: analysis of brazilian academic production - Santos Junior, José da Silva; Real, Giselle Cristina Martins (Universidade Estadual de Campinas, 2019)
The objective of this study is to analyze the scenario of dissertations and theses production on higher education dropout in the year 2000 to 2018, in order to identify and investigate if and how the institutional factor has been pointed out as one of the responsible for the phenomenon of dropout in Brazilian institutions. It’s a qualitative research, known as the state of knowledge, resorting to the works in the banks of theses and dissertations of Brazilian Institute of Information on Science and Technology (Ibict) and Higher Education Personnel Improvement Coordination (Capes). We selected 267 dissertations and 32 theses, in which we analyze the titles, abstracts and keywords and, in some cases, there was a cross-sectional reading, involving the introduction and the final considerations. Subsequently, we identified 11 papers, which referred to the institutional factor, on which we performed the full reading. The theoretical framework starts from the perspective of student integration, by Tinto (1975), and Pedagogy of Affiliation, by Coulon (2017). The results indicate that:  the main research trend refers to a case study in face-to-face courses of federal universities; dissertations and theses little explore the institutional factor for dropout. It is needed institutional policies for the control of dropout and researches that analyze the institutionalization of these policies in Brazilian institutions are important.